Developing Mind Body Hunger Mastery - Siri Khalsa-Zemel; Kara L. Vander Linden (Grounded Theory Review: An International Journal)
This quest to explore hunger using classic grounded theory was sparked within a dietitian who was hungry for a deeper understanding of her patients. The high rates of overweight and obesity in the United States are alarming and the mind body link with hunger is a rich area for study. The grand tour question for this classic grounded theory study was “can you tell me about your experience with hunger?” The resulting theory touches on some of the fastest growing fields of study in the United States: overweight and obesity, mind body medicine, and personal development. The substantive theory of developing mind body hunger mastery depicts two types of hunger, physical hunger and abstract hunger, each requiring separate nourishment processes. Nourishment can be interrupted at the physical and the abstract levels, leading to hunger confusion and hunger suffering. It may be possible to escape this maze through self-awareness and development of mind body hunger mastery.